Development and evaluation of a multi‐antigen peptide ELISA for the diagnosis ofChlamydia trachomatis‐related infertility in women. Issue 9 (September 2016) - Menon, Shruti; Stansfield, Scott H.; Logan, Benignus; Hocking, Jane S.; Timms, Peter; Rombauts, Luk; Allan, John A.; Huston, Wilhelmina M.
Abstract : N/A: Chlamydia trachomatis results in tubal factor infertility in some women. Diagnosis of this tubal infertility is difficult and typically involves laparoscopy or hysterosalpingography to detect the tubal blockages. Numerous serological tests have been developed; however, they are presently not used for diagnosis without subsequent surgical investigation during the infertility investigation. This study aimed to develop a highly specific serological assay for chlamydial tubal factor infertility in women that could be used to recommend direct progression to in vitro fertilization (IVF) treatment for women who are positive. Women were recruited from a variety of settings including women seeking fertility treatment, sexual health and general practitioner (GP) consultations or antenatal care ( n =259). The serological assay was developed using sera from a large group of women by using infertile microimmunofluorescence (MIF)‐positive women with tubal damage as the positives compared to infertile or acute infection and/or fertile controls (negatives). The new multi‐peptide ELISA was highly specific for the detection of tubal factor infertility ( P =0.011) compared to another ELISA ( P =0.022) and MIF ( P =0.099). The sensitivity of the assay should be improved before clinical utility. Potentially, a two‐step testing protocol could be used during the initial infertility investigation, where MIF followed by a highly specific ELISA could be used to recommend direct progression to IVF for women who are positive.